The value of public sector audit: Literature and history. Issue 1 (14th November 2017) - Hay, David; Cordery, Carolyn
Abstract : This paper explores the value of financial statement auditing in the public sector. The study applies theory about auditing from the private sector as well as the public sector to explore ways in which public sector auditing can be expected to be valuable. It shows that there are a number of complementary explanations that can be applied to examine the value of public audit, including agency, signaling, insurance, management control, governance and confirmation explanations. The evidence from research and history is generally consistent with the agency and management control explanations. There is some support for the signaling and insurance explanations, while research evidence suggests that governance has differing impact in the public sector compared to the private. The confirmation hypothesis is also potentially relevant. Reviewing the history of the development of public sector auditing functions shows that at least some developments were consistent with explanations such as agency theory and management control. Auditing in the public sector is an area where more research is valuable. The paper concludes with a discussion of issues for further investigation.